2018
DOI: 10.1002/jor.24127
|View full text |Cite
|
Sign up to set email alerts
|

Improved biomechanics of two alternative kyphoplasty cementation methods limit vertebral recollapse

Abstract: The clinical efficacy of vertebral cement augmentation for compression fractures (VCFs) remains undetermined. Recent studies have shown that refracture and progression of deformity may occur after augmentation with significant clinical consequences. Vertebral body height loss following kyphoplasty has also been observed with cyclic loading. We hypothesized that height loss is partly due to lack of cement fill past the margin of cancellous bone created by balloon expansion with subsequent failure under load. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…This is especially relevant for fractures affecting the posterior wall of the vertebral body or in patients with tumoral lesions in the verrtebral body. Additionally, a recent biomechanical study revealed that using a curette before balloon kyphoplasty may reduce the rates of vertebral height loss after kyphoplasty, which could have been related to a lack of cement interdigitation with the cancellous bone of the vertebral body adjacent to the cavity created by the balloon in the noncurette group . This study also demonstrated greater filling of the vertebral bodies by cement in the curette group, a difference that reached statistical significance.…”
Section: Introductionmentioning
confidence: 65%
“…This is especially relevant for fractures affecting the posterior wall of the vertebral body or in patients with tumoral lesions in the verrtebral body. Additionally, a recent biomechanical study revealed that using a curette before balloon kyphoplasty may reduce the rates of vertebral height loss after kyphoplasty, which could have been related to a lack of cement interdigitation with the cancellous bone of the vertebral body adjacent to the cavity created by the balloon in the noncurette group . This study also demonstrated greater filling of the vertebral bodies by cement in the curette group, a difference that reached statistical significance.…”
Section: Introductionmentioning
confidence: 65%